EFFECT OF LOCAL AND IMPORTED BIOFERTILIZERS ON GROWTH AND YIELD OF POTATO - & et al., Al Rubaye (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
A field experiment was carried out in loam soil at the research station of the College of Agriculture University of Baghdad, using randomized complete block design. The experiment included three local biofertilizers types (Bacillus megaterium, Pseudomonas fluorescens, Azotobacter chrococcum) and an imported biofertilizer (Nitrosoil) by Iraqi’s Ministry of Agriculture, beside, two levels of mineral fertilization (50% and 75%) of the mineral fertilizer recommendation with use of two types of carriers (corn cobs residue, broth liquid medium) in addition to the control treatments. Three replicates for each treatment were used on growth and yield of potato. The results showed a significant effect of biofertilizer in most of the studied traits. The results also showed that use of local biofertilizer with (75%) of mineral fertilizer increased plant height, dry weight of the total vegetables part of plants and total yield tuber with value reached 73.53 cm, 2.48 and 21.97 Mg ha-1 12.33  respectively, compared with the imported biofertilizer and control treatments, while the results showed that the use of half of the fertilizer recommendation with local bio-fertilization carried with liquid medium was sufficient to reach the best amount of nitrogen and phosphorus concentration by the plants in which the value reached to 2.62%, 0.79% compared to imported biofertilizer treatment which showed superiority in the amount of potassium absorbed to the same level of the recommendation and the value  was 1.20%.